2022
DOI: 10.1126/sciadv.abo1733
|View full text |Cite
|
Sign up to set email alerts
|

Gene drive mosquitoes can aid malaria elimination by retarding Plasmodium sporogonic development

Abstract: Gene drives hold promise for the genetic control of malaria vectors. The development of vector population modification strategies hinges on the availability of effector mechanisms impeding parasite development in transgenic mosquitoes. We augmented a midgut gene of the malaria mosquito Anopheles gambiae to secrete two exogenous antimicrobial peptides, magainin 2 and melittin. This small genetic modification, capable of efficient nonautonomous gene drive, hampers oocyst development in bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…In our previous study, we demonstrated that overexpressing exogenous AMPs in the posterior mosquito midgut post-bloodmeal could impact P. falciparum infection, holding promise for potential malaria transmission blockade [10]. Consequently, the intended outcome of REL2 overexpression was the transcriptional activation of Imd pathway-controlled AMPs in the posterior midgut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that overexpressing exogenous AMPs in the posterior mosquito midgut post-bloodmeal could impact P. falciparum infection, holding promise for potential malaria transmission blockade [10]. Consequently, the intended outcome of REL2 overexpression was the transcriptional activation of Imd pathway-controlled AMPs in the posterior midgut.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier work has already demonstrated the successful modification of the An. gambiae CP locus (along with other midgut loci) to accommodate such antimalarial effectors and their corresponding gRNA [10, 11]. These modifications demonstrated high non-autonomous homing rates and minimal fitness costs, highlighting the potential of IGD as a powerful tool for driving the expression of antimalarial effectors in mosquito populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this technology has been applied on An. gambiae , resulting in a successful halting of Plasmodium development within the genetically modified mosquitoes, as well as compromising the survival of the homozygous transgenic females ( Hoermann et al, 2022 ). In addition, other gene editing methods, such as the application of homing endonuclease genes (HEG) have been explored to control the malaria vectors ( Windbichler et al, 2007 ; Deredec et al, 2011 ).…”
Section: Manipulation Of Vital Biological Functionsmentioning
confidence: 99%
“…Authors have also paired their transgenic mosquitoes expressing melittin and magainin with Cas9, which resulted in high levels of homing of the transgene. They predicted the probabilities of malaria elimination in 3 field scenarios, low, medium, and high transmission, and concluded that elimination of malaria would be achieved quickly in a low transmission field setting (Hoermann et al 2022). In March 2023, a major scientific achievement in the field has been announced, the engineering of the first transgenic (nongene-drive) mosquito in the African continent, in a joint effort by Transmission Zero, a global scientific program led by scientists at Imperial College London and the Ifakara Health Institute of Tanzania, in partnership with the Tanzanian National Institute of Medical Research.…”
Section: Transgenic Approachesmentioning
confidence: 99%